Investment responses to tax policy under uncertainty - Guceri, I; Maciej, A (Saïd Business School, 2020)
How does economic uncertainty affect investment responses to tax policy? We exploit a natural experiment in which two very similar investment subsidies were implemented in the same country, two years apart: once during a period of economic stability, and once during a period of very high uncertainty. Exploiting sharp discontinuities in eligibility and using rich administrative data, we find that, under low uncertainty, tax incentives have strong positive effects on average investment. Under high uncertainty, however, the story is different: there is vast heterogeneity in investment responses, with the firms that are sheltered from elevated uncertainty still responding strongly to the policy, and the firms that are exposed to high uncertainty driving a drop in responses. This implies that periods of stability offer an important policy opportunity to encourage investment, and that the impact of stimulus in crises depends on the distribution of firms in their exposure to elevated uncertainty.